The Analysis of Visitor Satisfaction Influenced by Tourist Attractions and Service Quality through Tourism Image in Kawung Tilu, Cikarang Timur, Bekasi Regency - Jamaludin Khalid (Ilomata International Journal of Management, 2023)
The objective of this study is to analyze how tourism attractiveness and service quality impact visitor satisfaction through the tourism image in the specific area of Kawung Tilu, Cipayung Village, Cikarang Timur District, Bekasi Regency. The research methodology is a quantitative descriptive approach comprising 120 respondents who are the visitors of the tourist sites. About 20 respondents are measured by the validity and the reliability testing, whereas 100 respondents will participate in the path analysis test. The findings reveal that tourism attractiveness has a positive influence on the tourism image. Similarly, the service quality positively affects the tourism image. In addition, tourism attractiveness has a positive impact on visitor satisfaction, as the service quality does. The tourism image acts as a mediator between tourism attractiveness and visitor satisfaction, aside from its direct effects. The results emphasize the significance in maintaining and enhancing tourism attractiveness and service quality to improve the tourism image and visitor satisfaction. In the context of developing a tourism village, it is crucial to consider these factors in order to deliberately create a positive experience for tourists and to effectively promote the tourism destination.